Evaluation of doctor's knowledge and practice with reference to clinical practice guideline (2009) Ministry of Health Malaysia on management of diabetes mellitus at Hospital Pulau Pinang - Iqbal, Muhammad Zahid (2014)
The available literature suggests that divergence of doctors with the recommendations of the guideline in the management of diabetes mellitus is the main reason for poor control of diabetes mellitus in patients. The current research in which 51 doctors were involved in the co-relational study conducted at Hospital Pulau Pinang (HPP). The aim was to evaluate the doctor's knowledge and prescription writing practices (diagnosis, screening and medication) on recommendations of Malaysian clinical practice guideline (CPG 2009) on diabetes mellitus, and factors concerning with the guideline adherence and diabetes mellitus control. Knowledge and attitude of doctors were evaluated by a validated questionnaire. Record of the patients written by 51 enrolled doctors to 1020 established diabetic patients (20 Record of the patients per enrolled doctor) with demographic and clinical information of the patients were noted by validated data collection tool. The taken record of the patients was classified as compliance or noncompliance with CPG 2009. SPSS version 20 was used for data analysis. Ap-value <0.05 was considered as statistically significant. The total 38 (74.5%) doctors were having adequate knowledge on recommendations of CPG 2009. Group of specialists were having good knowledge as compared with medical officers and house officers (p-value <0.03). Doctors were having highly positive and welcoming attitude on recommendations of CPG 2009 with mean attitude score of 36.64 ± 3.93 points ranging from 35-40 points on 50 point scale.Statistically strong association (p-value< 0.001) was observed between doctors knowledge and practice score. Seven hundred and fifty (73.5%) patients were receiving guidelines compliance therapy.